Multi function iron board / Muhammad Dinie Mohd Yusri - Mohd Yusri, Muhammad Dinie (2023)
This study is intended to provide an overview of product development for unique goods that will be developed, manufactured, and fabricated for a specific market and industry. My objective is to produce an iron board that supports an environmentally friendly function by allowing people to utilize a multifunction iron board that includes mirrors, placeholder for iron with security lock, and a night light. My product has transformed the existence of iron boards into new features and design alterations that may meet the needs of Malaysians. As a result, my goals are to discover solutions to difficulties and to present people with a better form of furniture that can address modern-day issues.